1996
DOI: 10.1002/(sici)1097-0142(19960101)77:1<193::aid-cncr31>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue sarcoma of the head and neck in children and adolescents

Abstract: Prognostic indicators for NRSTS include completeness of tumor resection and the development of recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…According to the Agency for Research on Cancer, soft-tissue sarcomas account for 4%-8% of cancers in patients up to 14 years of age (2,(35)(36)(37). Whereas head and neck primary sarcomas represent only 5%-15% of all adult sarcomas, 35% of all sarcomas in the pediatric population manifest in the head and neck (38 -40).…”
Section: Acquired Lesions Sarcomas Of the Head And Neckmentioning
confidence: 99%
“…According to the Agency for Research on Cancer, soft-tissue sarcomas account for 4%-8% of cancers in patients up to 14 years of age (2,(35)(36)(37). Whereas head and neck primary sarcomas represent only 5%-15% of all adult sarcomas, 35% of all sarcomas in the pediatric population manifest in the head and neck (38 -40).…”
Section: Acquired Lesions Sarcomas Of the Head And Neckmentioning
confidence: 99%
“…4 These tumors are more common in childhood, and up to 33% occur in the head and neck region. 5,6 The skull base is one of the common anatomic regions involved in head and neck sarcomas. 7,8 The majority of these patients present with symptoms, the most frequent of which is a painless mass.…”
mentioning
confidence: 99%
“…There is a slight male predisposition for sarcomas tumor. 13,14 The mean age in out sample was 7.79 years; males predominated slightly (54.17%) compared to females (45.83%). Lyos et al found similar results in a study of 134 patients where the mean age was 7 years and the male to female ratio was 1.2:1.…”
Section: Discussionmentioning
confidence: 94%